2017
DOI: 10.1080/07420528.2017.1388253
|View full text |Cite
|
Sign up to set email alerts
|

Repercussions of hypo and hyperthyroidism on the heart circadian clock

Abstract: Myocardial gene expression and metabolism fluctuate over the course of the day in association with changes in energy supply and demand. Time-of-day-dependent oscillations in myocardial processes have been linked to the intrinsic cardiomyocyte circadian clock. Triiodothyronine (T3) is an important modulator of heart metabolism and function. Recently, our group has reported time-of-day-dependent rhythms in cardiac T3 sensitivity, as well as, T3-mediated acute alterations on core clock components. Hypo and hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…Thyroid receptors expression shows circadian variation in hepatocytes and adipose tissue in mice [17] and the interruption of this physiological rhythm is another possible mechanism to be considered when analysing the effect of sleep short duration and or misalignment. Some other experimental data supports that hypo and hyperthyroidism affect the clock genes tissue expression; for example, an experimental study showed a significant effect on myocardial metabolism related to the circadian rhythm [18].…”
Section: Discussionmentioning
confidence: 85%
“…Thyroid receptors expression shows circadian variation in hepatocytes and adipose tissue in mice [17] and the interruption of this physiological rhythm is another possible mechanism to be considered when analysing the effect of sleep short duration and or misalignment. Some other experimental data supports that hypo and hyperthyroidism affect the clock genes tissue expression; for example, an experimental study showed a significant effect on myocardial metabolism related to the circadian rhythm [18].…”
Section: Discussionmentioning
confidence: 85%
“…Statistical analyses were performed using one-and twoway ANOVA, as well as repeated measures ANOVA, as described previously (Bray et al 2013(Bray et al , 2008Peliciari-Garcia et al 2018). Briefly, analyses were performed with Graph Pad Prism (GraphPad Software version 6.01, San Diego, CA, USA) to investigate the main effects of time and/or nutritional status, followed by Bonferroni post hoc analyses for pair-wise comparisons (indicated in Figures).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, analyses were performed with Graph Pad Prism (GraphPad Software version 6.01, San Diego, CA, USA) to investigate the main effects of time and/or nutritional status, followed by Bonferroni post hoc analyses for pair-wise comparisons (indicated in Figures). Cosinor analyses were performed for assessment of mesor (average value over a 24-h period), amplitude (peak-tomesor difference) and acrophase (timing of peak; ZT), as described previously (Peliciari-Garcia et al 2018). When appropriate, Student's t-test was also applied to these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…30 Although the circadian profile of TSH in humans is well documented, the underlying mechanism of such circadian regulation has not been explored. 32 31 The expression levels of the BMAL1 were upregulated in tissue samples of follicular (FTC) and papillary thyroid carcinoma (PTC), as compared with normal thyroid tissue and benign nodules, whereas CRY2 was downregulated in both FTC and PTC.…”
Section: Clock Genes and Thyroid Disordersmentioning
confidence: 99%
“…31 Either increased or decreased T3 levels regulated the expression of BMAL1 and ROR in rat cardiomyocytes, while only decreased T3 levels altered PER2 expression in rat cardiomyocytes. 32…”
Section: Clock Genes and Thyroid Disordersmentioning
confidence: 99%